2013
DOI: 10.1016/j.eatbeh.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive sensitivity deficits in women recovered from bulimia nervosa

Abstract: Self-report studies suggest that patients with Bulimia Nervosa (BN) evidence difficulties with interoceptive awareness. Indeed, interoceptive deficits may persist after recovery of BN and may be a biological trait that predisposes symptom development in BN. However, no studies to date have directly assessed interoceptive sensitivity, or accuracy in detecting and perceiving internal body cues, in patients with or recovered from BN. Nine women who had recovered from BN and 10 healthy control women completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 41 publications
3
67
1
Order By: Relevance
“…While Eshkevari et al, (2014) found no differences in heartbeat detection accuracy in anorexic and bulimic participants, relative to healthy controls, Klabunde, Acheson, Boutelle, Matthews, and Kaye (2013) observed that recovered bulimic participants were less accurate relative to controls on this task (r ¼ 0.65, [n ¼ 19]). This is consistent with two further findings.…”
Section: Psychiatric Conditions and Individual Differences In Interocmentioning
confidence: 85%
“…While Eshkevari et al, (2014) found no differences in heartbeat detection accuracy in anorexic and bulimic participants, relative to healthy controls, Klabunde, Acheson, Boutelle, Matthews, and Kaye (2013) observed that recovered bulimic participants were less accurate relative to controls on this task (r ¼ 0.65, [n ¼ 19]). This is consistent with two further findings.…”
Section: Psychiatric Conditions and Individual Differences In Interocmentioning
confidence: 85%
“…4 Altered activity in the ACC and OFC has been observed in patients with bulimia nervosa during impulse-control tasks, which has been associated with self-regulatory deficits 12,13 (i.e., an inability to inhibit impulses in favour of a delayed reward). Although it plays an important role in the processing of interoception-reward signals, 53 disturbed insula response to sucrose taste has been implicated in interoceptive deficits (i.e., reduced ability to feel full or hungry) in individuals with bulimia nervosa. 3,53 It could be speculated that patients with bulimia nervosa may be impaired in a series of reward-related processes, which contributes to an inability to accurately identify emotional significance, generate appropriate behaviours and make decisions concerning eating and bodily stimuli.…”
Section: Functional Brain Network In Bulimia Nervosamentioning
confidence: 99%
“…Although it plays an important role in the processing of interoception-reward signals, 53 disturbed insula response to sucrose taste has been implicated in interoceptive deficits (i.e., reduced ability to feel full or hungry) in individuals with bulimia nervosa. 3,53 It could be speculated that patients with bulimia nervosa may be impaired in a series of reward-related processes, which contributes to an inability to accurately identify emotional significance, generate appropriate behaviours and make decisions concerning eating and bodily stimuli. 22 Our findings also pointed to a less commonly considered region in patients with bulimia nervosa -the thalamus.…”
Section: Functional Brain Network In Bulimia Nervosamentioning
confidence: 99%
“…In comparison to controls, the first study examined a small number of women recovered from BN who had also never met prior criteria for AN (Klabunde et al, 2013), the second study examined participants with current AN and BN diagnoses (Eshkevari et al, 2014), while the third study examined women with a current BN diagnosis (Pollatos and Georgiou, 2016). The first and third studies used the heartbeat counting version of the HBPT (Schandry, 1981), which required participants to count how many heartbeats they could detect within specific time intervals.…”
Section: Resultsmentioning
confidence: 99%
“…The first study found that women recovered from diagnostically “pure” BN (no participants had a prior diagnosis of AN) demonstrate significantly lower interoceptive accuracy in comparison to controls (Klabunde et al, 2013); these participants did not have physiological complications that go alongside a BN diagnosis, which may make it easier to examine the neurobiology that may lead one to developing an eating disorder. The second study compared the BN and control groups during post-hoc comparisons and did not detect significant findings between groups (Eshkevari et al, 2014).…”
Section: Resultsmentioning
confidence: 99%